The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c8bm01535j
|View full text |Cite
|
Sign up to set email alerts
|

Second harmonic generation microscopy of collagen organization in tunable, environmentally responsive alginate hydrogels

Abstract: We fabricated photocrosslinked, environmentally responsive alginate hydrogels for tissue engineering applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…Some dead EthD-1-positive cells were observed on the PLGA-only sponge. It has previously been observed that cell morphology can be controlled by the viscosity of substrates and that gel stiffness can affect cell proliferation [ 72 , 73 ]. The cells in the 50% HA hydrogel showed better spreading and increased cell number because 50% HA had a lower viscosity (Figure S 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some dead EthD-1-positive cells were observed on the PLGA-only sponge. It has previously been observed that cell morphology can be controlled by the viscosity of substrates and that gel stiffness can affect cell proliferation [ 72 , 73 ]. The cells in the 50% HA hydrogel showed better spreading and increased cell number because 50% HA had a lower viscosity (Figure S 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Second harmonic generation (SHG), in which two lower energy photons are upconverted to a single high-energy photon with twice the energy, occurs in ordered non-centrosymmetric materials. Notably fibrillar collagen, a key component of the ECM, exhibits a strong SHG response [ 237 ] which can be exploited for label-free visualization tissue remodelling in response to PM exposure and structural imaging of lung tissue scaffolds [ 238 ] and other collagen-based hydrogels [ 239 ]. SHG microscopy has also been applied to visualize other biomolecular assemblies such as microtubules [ 240 ].…”
Section: High-resolution Imaging Of Respiratory Modelsmentioning
confidence: 99%
“…SHG has also been used to investigate collagen remodeling and the role of enzymes released from the cells in crosslinking collagen fibers [ 148 ]. Collagen fibers that are newly deposited by cells encapsulated in alginate hydrogels are also readily visualized by SHG [ 149 ].…”
Section: Photon-based Techniquesmentioning
confidence: 99%